Main foreign policy characteristics of European dwarf states in the 20th century - Alimova-Nefedova, Mariia Borisovna (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2025)
This article explores the key features of the foreign policy of four European dwarf states that managed to retain their status as independent political and territorial entities by the start of the 20th century: the Principality of Andorra, the Principality of Liechtenstein, the Principality of Monaco, and the Most Serene Republic of San Marino. The study highlights how, due to their similarities in size and historical circumstances, these states’ foreign policies not only share common traits, but have also evolved in similar ways over time. The article concludes that while there are some parallels between the foreign policies of these dwarf states and other small countries, their strategies, concepts, and instruments are distinct and tailored to their specific contexts.